Comparison of microwave-assisted chemicals in demulsification of water-in-crude oil emulsions - Chew, Jun Jian (2012)
Demulsification(emulsion breaking or emulsions destabilizing)is important in many industry applications such as the petroleum industry,painting and waste-water treatment in environmental technology.Chemical and microwave heating demulsification is the most widely used method of demulsifying the water-in-crude oil emulsions and both methods accelerate the emulsion destabilizing process.This research combined the chemical with microwave-assisted to increase the efficiency of demulsification and reduce the chemical usage to prevent any environmental issues. The effect of chemical demulsification with microwave-assisted operations on the stability and properties of water-in-crude oil emulsions was assessed experimentally by using different types of demulsifiers which are Amine and Polymeric demulsifiers with microwave heating.By using the sample of water-in-crude oil emulsions which prepared by adding artificial emulsifiers(Span 83) which had formed the most stable emulsion after the complete screening of stability part was conducted,the chemical demulsifiers were added in the emulsions to break the emulsion with the assistant of microwave heating to increase the performance.The research found that Hexylamine and Cocoamine had the high efficiency of the demulsification with the assistant of microwave heating which was different from the conventional method but the latter was better as it was more environmental friendly. Overall results show that demulsification by microwave heating was faster as compared to the gravity sedimentation and it does not require much chemical additions to boost the breaking of the emulsion.